Potential of orchid as antifungal agent resources: a scoping review - Furqi Sholekhatun Sityardi; Sufi Desrini (Indonesian Journal of Pharmacology and Therapy, 2021)
In 2017, one billion people contracted fungal infection with 11.5 million people contracted life-threatening infection and 1.5 million death per year. Orchid is a plant that grows in tropical and sub-tropical countries, the same places where fungal infection occurrence is high. On previous studies reported that orchid contains alkaloids and polyphenols such as flavonoid, and phenol acid. The review aimed to identify the orchid as a potential antifungal resource. A scoping review was used. The type of articles reviewed were original articles obtained from five electronic journal databases published within 2012-2021. Three articles reported similar result which was that orchid extract has a significant antifungal activity although the part of plant used was different, ranging from the root, to the leaf. Two articles reported a specific antifungal activity against Candida albicans while the remaining one against Trichophyton rubrum. In conclusion, the root, leaf, branch, and flower extracts of orchid is potential antifungal resources.